(untitled) (Fiep Bulletin - online, 2012)
The objective of this study was to verify some indicators of lifestyle and Practice of Physical Activity in Leisure, Individual Health Perception, Perception of Stress and smoking of workers in companies served by SESIGE in Santa Catarina, in order to become a reference to used in future research. This survey was conducted in 2011, through research proposals in 2010, which applied to employees of companies assisted by the Program SESIGE Santa Catarina. It is a descriptive and quantitative. Processing, data processing and statistical analysis were performed using the Sphinx software version 5.1.0.5. Data analysis considered the number of citations and we used univariate and bivariate statistics. To evaluate the association between two variables used the chi-square adopting the statistical significance level of 99.9% (p <0.01). 35,077 workers participated in the survey, belonging to 214 companies assisted by the Program SESIGE in Santa Catarina, with approximately 51.0% (17,767) were men, predominantly aged 35 years at 66.7% (23,409) and about 73.0% (25,462) work in manufacturing. It was found that 41.3% (14,490) of workers in the industry of the state is physically inactive during leisure time, 10.6% (3712) reported smoking, 18.6% (6530) of people expressed a negative perception in relation to stress and 18.2% (6388) of people expressed a negative perception regarding their own health. It is concluded that the health indicators and lifestyle checked enable the industry to invest in raising the level of health and well-being of workers, the SESI, periodically update the information about your field, comparing data and directing choices that lead to greater effectiveness and efficiency in response to the client.